APLIKASI E-COMMERCE BERBASIS DSS PADA TOKO KUE KUMALA - Stephen Prihandana (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Making E-Commerce application program based cake shop jade DSS is a computerized system of Ecommerce. Making E-Commerce application program based on Pastry Shop Kumala DSS was created to address the problems found in the manual of sale system that can slow the performance of a business. The method used is the SDLC (System Development Life Cycle) which consists of four phases: planning, analysis phase, design phase and implementation phase. The programming language used is PHP and the database used is MySQL.. Key words E-Commerce, DSS, dan SDLC